Injury prevention among friends: The benefits of school connectedness. Issue 6 (17th July 2014) - Chapman, R.L.; Buckley, L.; Reveruzzi, B.; Sheehan, M.
ABSTRACT: Unsafe road behaviors, violence and alcohol use, are primary contributors to adolescent injury. Research suggests that adolescents look out for their friends and engage in protective behavior to reduce others' risk‐taking and that school connectedness is associated with reduced injury‐risks. This study examined the role of school connectedness in willingness to protect and prevent friends from involvement in alcohol use, fights and unlicensed driving. Surveys were completed at two time points, six months apart, by 545 13–14 year olds from seven Australian high schools. Females were significantly more likely than males to report willingness to protect their friends. School connectedness significantly and positively predicted willingness to protect across all three injury‐risk behaviors, after accounting for sex and own involvement in injury‐risk behaviors. School connectedness may therefore be an important factor to target in school‐based prevention programs, both to reduce adolescents' own injury‐risk behavior and to increase injury prevention among friends.